A Medical Image Encryption Scheme Based on a Modified CKBA - Sadou, Yousra; Dib, Samira; Grimes, Morad (International Multi-Conference on Systems, Signals, and Devices, 2022)
The rapid growth in Internet exchange traffic for medical images justifies the creation of appropriate tools to guarantee the quality and confidentiality. Cryptography is an effective solution that can be implemented routinely to encrypt those digital media. On the basis of a one dimensional logistic map, the chaotic key-based algorithm (CKBA) has been proposed in last decades. Nevertheless, it has been proved that the existing approach is extremely sensitive to several attacks, and the authors claims of increased security against these attacks have merely been exaggerated. Moreover, an uneven outcome is produced by the chaotic logistic map. In this article, we improve the CKBA algorithm by changing the logistic map to a modified one. The performances of the presented encryption model remain very good. The suggested algorithm is validated using a number of security analyses. The NPCR is enhanced over 99.61% and UACI over 33.46%, and entropy is noticed to be near to 7.9769. As a result, the new encryption has substantially greater security.